Agricultural damage in mokama tal REGION by flood; AND its conserVation: a geographical description - Kumar (NET), Anil (International Journal of Psychosocial Rehabilitation, 2020)
Tal is a large piece of land in Mokama under the Patna district of Bihar. Many people think it is the largest Thar region in the world. It extends to the backwaters of the Ganges during the monsoon and gives the onlookers the impression of the ocean. In other seasons, it provides very fertile land for agriculture.Tal is located in the Kiul-Harohar basin, with an area of 1062 square kilometers (410 square miles). It is a dish-shaped depression that extends from Fathu in the west to Lakhisarai in the east. Its width varies from 6 to 17 kilometers. It is close to and almost parallel to the right bank of the Ganges.It has been human nature to struggle with the problem (flood) and go forward towards development by coordinating with it. The research is an attempt in the field so that the common men in Mokama Tal can look forward to overcome this struggle and coordination with the government for the development in the area.